PENGEMBANGAN WIKISPACE SUPPORT PADA POKOK BAHASAN TRIGONOMETRI DI KELAS X SEKOLAH MENENGAH ATAS (SMA) - Valensia, Lydia (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2014)
Wikispace is an online service for creating and hosting the wikis. Wikispace provide features that allow the learning process in groups organized by regulating members of wikis to the project team, each team will have a page, file and license its own wikis. This research aimed to produce (1) wikispace support on Trigonometry topic grade X High School who meet the criteria valid and practical in the process of learning mathematics, (2) determine the potential effect wikispace support to the activities and outcomes of learners. The method of development research is used. Prototype strategy implemented during the development process. Data collection using walk through, observations, video- in-class activities, and questionnaires. All data collected were analyzed by descriptive qualitative. DOI: https://doi.org/10.22342/jpm.8.2.1913.86-102